Mobile Learning Terintegrasi Sensor Real-Time: Peningkatan Kualitas Pembelajaran Fisika Klasik melalui Eksperimen dan Analisis Data - Gaguk susanto , Syahminan, Wiji setyanings (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2025)
Abstract The use of mobile technology in education has developed rapidly, especially through Android-based applications. This study aims to examine the effectiveness of an interactive Android application in enhancing students’ understanding of physics concepts in senior high school. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects were 60 eleventh-grade science students from a senior high school in Malang Regency, divided into an experimental group and a control group, each consisting of 30 students. The experimental group used an Android application developed for learning Newton's Laws, while the control group used conventional methods. The results showed a significant improvement in conceptual understanding in the experimental group compared to the control group. These findings indicate that Android applications can serve as effective and engaging learning media for students. K